Gaseous disinfection of Cryptosporidium parvum oocysts. - Fayer, R (1996)
Purified oocysts of Cryptosporidium parvum suspended in approximately 400 microliters of phosphate-buffered saline or deionized water in microcentrifuge tubes were exposed at 21 to 23 degrees C for 24 h to a saturated atmosphere of ammonia, carbon monoxide, ethylene oxide, formaldehyde, or methyl bromide gas. Controls were exposed to air. Oocysts in each tube were then rinsed and resuspended in fresh, deionized water, and 1 million oocysts exposed to each gas were orally administered to each of three to six neonatal BALB/c mice in replicate groups. Histologic sections of ileum, cecum, and colon tissues taken from each mouse 72 h after oral administration of oocysts were examined microscopically to determine if infection had been established. All 15 mice given oocysts exposed to carbon monoxide had numerous developmental stages of cryptosporidium in all three intestinal segments. Of 10 mice given oocysts exposed to formaldehyde, 6 had a few developmental stages of cryptosporidium in the ileum. No mice given oocysts exposed to ammonia, ethylene oxide, or methyl bromide were found to be infected. These findings indicate the efficacy of these low-molecular-weight gases (ammonia, ethylene oxide, and methyl bromide) as potential disinfectants for C. parvum oocysts where soil, rooms, buildings, tools, or instruments might be contaminated.